A novel surface plasmon-based sensor for liquid refractive index measurement with biochemical sensing capabilities - Yan, Shubin; Yang, Weijie; Wang, Chong; Yan, Zhaokun; Wu, Taiquan (Frontiers in Physics, 2025)
In this work, a highly sensitive wavelength sensor based on a metal-insulator-metal (MIM) waveguide is presented to increase sensitivity and quality factor by optimizing critical structural factors that control sensing performance. The sensor utilizes a waveguide and a circular ring structure (DTRS) with disk and T-shaped cavities to excite the Fano resonance, and the refractive index is sensed at the nanoscale by detecting the resonance wavelength shift. By systematically investigating the coupling and correlation mechanism between device architecture and operating parameters on performance indexes, a full-parameter optimization strategy is adopted to establish the device configuration with the best performance. The sensitivity of the device can reach 2820 nm/RIU, and the FOM value can reach 60, which is of great value in the fields of biomolecule detection, environmental monitoring and chip integration.